The trend of 3D printing in higher level TVET skill - Kumaran, Kadirgama; Wan Sharuzi, Wan Harun (2020)
Additive manufacturing is a recent trend in production processes owing to its many benefits around the globe. It can be defined as the process of producing parts through the deposition of material in a layer-by-layer technique. It has been the most searchable research topic since 2000. According to Frost and Sullivan, the value of additive manufacturing is expected to grow at a rate of 15% from US$5.31 billion in 2015 to US$21.50 billion in 2025. The industries that are going to contribute 51% by 2025 are aerospace, automotive, and medical industries.